Kiwi value chain in Arunachal Pradesh: issues and prospects - Gyanendra Mani; Ashish Kundra; Azimul Haque (Agricultural Economics Research Review, 2023)
This paper examines some issues related to the production and marketing of kiwi in Arunachal Pradesh, the largest producer of kiwis in India. It contributes 56.5% of the total 8.5 thousand tons of kiwis produced in the country. India imports 75% of its domestic demand for fresh kiwis and, therefore, there is huge scope to upscale kiwi production in north-eastern states in general and Arunachal Pradesh in particular. However, developing an efficient value chain is a challenge because of several infrastructural and institutional constraints like the non-availability of reliable data on production, lack of research and extension support, lack of organized marketing and post-harvest infrastructure, poor credit support, etc. A few solutions suggested for upscaling the kiwi production are : the formation of ‘Kiwi Producers Groups (KPGs)’, a dedicated research centre for kiwi, and sufficient credit flow to farmers.